Constituintes químicos e atividade antioxidante de extratos das folhas de Terminalia fagifolia Mart. et Zucc - Ayres, Mariane Cruz Costa; Chaves, Mariana H.; Rinaldo, Daniel [UNESP]; Vilegas, Wagner [UNESP]; Vieira Júnior, Gerardo Magela [UNESP] (Sociedade Brasileira de Química, 2009)
Phytochemical investigation of ethanolic leaves extracts of T. fagifolia led to the isolation of (+)-catechin, sitosterol-3-O-β-D-glucopyranoside, α- and β-tocopherol, a mixture of lupeol, α- and β-amyrin, sitosterol and a mixture of glicosid flavonoids (CP-13). The structures of these compounds were identified by ¹H and 13C NMR spectral analysis and comparison with literature data. Absolute configuration of the catechin was determinate by circular dichroism. Antioxidant activity (EC50), evaluated by 2,2-diphenyl-1-picrylhidrazyl (DPPH) assay system, decreased in the order: (+)-catechin > hydroalcoholic fraction > CP-13 > aqueous fraction > EtOH extract.
Chemical constituents and antioxidant activity from leaves extracts of Terminalia fagifolia Mart. et Zucc
Keywords: Terminalia fagifolia; DPPH; antioxidant activity